Epidemiological Study of The Microbial Causes of Diarrhea in Children in Najaf Governorate, Iraq - Elham Jawad Kadhum (International Journal of Pathogens, 2026)
The current study included a survey of the microbial causes of diarrhoea among children attending Al- Zahra Teaching Hospital for Maternity and Children in Najaf Governorate and Al-Furat Al-Awsat Hospital in Kufa District. 150 samples were collected, ranging in age from one day to seven years, over a three-month period, from 1/10/2024 to 30/12/2024. The direct swab and stool concentration method was used to examine the stool. The results showed significant differences in favour of the age group (4–6 years) between males and females, in favour of females for bacterial infections (P < 0.05). The study also showed significant differences in favour of males for fungal, parasitic, and viral infections (P < 0.05) at a rate of 65%, while there were significant differences in favour of Salmonella bacteria (P < 0.05) at a rate of 63%, 53%, and 60%, respectively. The results also showed significant differences in the age group (4–6 years) for E. histolytica (P < 0.05) at a rate of 77.8%, and significant differences in the age group (day–2 years). In Favor of fungal infections, there was a rate of 96.7% within the age group (4–6 years) (P < 0.05) at a rate of 93.6%, and significant differences. The study also showed that the highest infection rate was during the month of December. First, most of the injuries occurred in the age group (4–6 years).
Keywords: Bacteria; Fertilizer; Infection; diarrhoea; fungi